Kurma, Gandum, dan Energi: Sains Gizi dalam Tafsir Ayat-Ayat Al-Qur’an - Andri Nirwana; Kuswardani Dyah Ayu Kusumaningrum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the integration between Qur’anic exegesis and molecular nutrition science, with a focus on carbohydrates as the main theme examined through the tafsir ilmi (scientific interpretation) approach. This research adopts a qualitative method based on a literature review, utilizing two primary sources: the Tafsir Ilmi published by the Ministry of Religious Affairs of the Republic of Indonesia and Tafsir Al-Jawahir by Tantawi Jauhari. Both represent interpretive models that attempt to bridge divine revelation with contemporary scientific findings. Carbohydrates are essential nutrients in the biological life of living beings. They function as the primary source of energy, structural components of cells, and regulators of metabolism. Although not explicitly mentioned in the Qur’an, several verses imply references to food items such as grains, dates, grapes, and honey—all of which are sources of carbohydrates. Interpreting these verses through scientific and molecular nutrition perspectives provides contextual understanding regarding dietary ethics and nutritional balance in Islam. The findings indicate that the Tafsir Ilmi of the Ministry takes a deductive-confirmatory approach by linking Qur’anic verses to modern scientific theories, while Tafsir Al-Jawahir adopts a more philosophical and reflective style, emphasizing the order of nature as a manifestation of divine law. Both interpretations highlight the importance of carbohydrates in sustaining life and maintaining ecological balance. This study concludes that the integration of exegesis and science contributes to a rational understanding of revelation and is relevant in addressing contemporary issues such as healthy eating patterns and the prevention of metabolic diseases. This research reinforces the importance of interdisciplinary Qur’anic studies in meeting the current needs of the Muslim community.